Correlative Live-Cell and Super-Resolution Imaging to Link Presynaptic Molecular Organisation With Function - Jackson, Rachel E.; Compans, Benjamin; Burrone, Juan (Frontiers in Synaptic Neuroscience, 2022)
Information transfer at synapses occurs when vesicles fuse with the plasma membrane to release neurotransmitters, which then bind to receptors at the postsynaptic membrane. The process of neurotransmitter release varies dramatically between different synapses, but little is known about how this heterogeneity emerges. The development of super-resolution microscopy has revealed that synaptic proteins are precisely organised within and between the two parts of the synapse and that this precise spatiotemporal organisation fine-tunes neurotransmission. However, it remains unclear if variability in release probability could be attributed to the nanoscale organisation of one or several proteins of the release machinery. To begin to address this question, we have developed a pipeline for correlative functional and super-resolution microscopy, taking advantage of recent technological advancements enabling multicolour imaging. Here we demonstrate the combination of live imaging of SypHy-RGECO, a unique dual reporter that simultaneously measures presynaptic calcium influx and neurotransmitter release, with posthoc immunolabeling and multicolour single molecule localisation microscopy, to investigate the structure-function relationship at individual presynaptic boutons.